GyrI-like proteins catalyze cyclopropanoid hydrolysis to confer cellular protection. Issue 1 (December 2017) - Yuan, Hua; Zhang, Jinru; Cai, Yujuan; Wu, Sheng; Yang, Kui; Chan, H.; Huang, Wei; Jin, Wen-Bing; Li, Yan; Yin, Yue; Igarashi, Yasuhiro; Yuan, Shuguang; et al.
Abstract GyrI-like proteins are widely distributed in prokaryotes and eukaryotes, and recognized as small-molecule binding proteins. Here, we identify a subfamily of these proteins as cyclopropanoid cyclopropyl hydrolases (CCHs) that can catalyze the hydrolysis of the potent DNA-alkylating agents yatakemycin (YTM) and CC-1065. Co-crystallography and molecular dynamics simulation analyses reveal that these CCHs share a conserved aromatic cage for the hydrolytic activity. Subsequent cytotoxic assays confirm that CCHs are able to protect cells against YTM. Therefore, our findings suggest that the evolutionarily conserved GyrI-like proteins confer cellular protection against diverse xenobiotics via not only binding, but also catalysis. GyrI-like proteins are small-molecule binding proteins that are widely distributed in prokaryotes and eukaryotes, with functions that are poorly characterized. Here, the authors identify GyrI-like proteins as cyclopropanoid cyclopropyl hydrolases that can confer resistance to cytotoxic cyclopropanoid compounds.